ПСИХОСОМАТИЧЕСКИЕ ЗАБОЛЕВАНИЯ: КОНЦЕПЦИИ И СОВРЕМЕННОЕ СОСТОЯНИЕ ПРОБЛЕМЫ - В. Э. Медведев (SINAPS LLC, 2013)
The article presents review of main conceptions of psychosomatic disorders' development. The most common mental disorders of non-psychotic level in general practice are described.